Child Victim Services in the Time of COVID-19: New Challenges and Innovative Solutions - Posick, Chad (American journal of criminal justice, 2020)
The impact of COVID-19 has been felt by all facets of the criminal justice system and victim services agencies. The ability to monitor and report maltreatment has been severely limited for organizations that work with children of abuse and neglect; this is particularly troubling given that abuse and neglect are likely to rise during times of distress and turmoil. The purpose of this paper is to discuss the importance of organizations that work with children exposed to maltreatment, highlight the novel approach of Child Advocacy Services, SEGA, Inc. (CASSEGA), the sponsoring agency for Court Appointed Special Advocates (CASA) and the Ogeechee Visitation Centers, in rural southeast Georgia and how the COVID-19 pandemic has challenged this work, and develop strategies that can be put into place to alleviate these challenges for other child-serving organizations.